The impact of primary and secondary processing steps on Campylobacter concentrations on chicken carcasses and portions. (April 2023) - Kingsbury, Joanne M.; Horn, Beverley; Armstrong, Bridget; Midwinter, Anne; Biggs, Patrick; Callander, Maree; Mulqueen, Kerry; Brooks, Michael; van der Logt, Peter; Biggs, Roy
Abstract: Campylobacteriosis is the most commonly notified foodborne disease in New Zealand and poultry meat is the major source for human infection. Carcasses and portions were sampled from key points along primary and secondary processing chains of three New Zealand poultry processors to determine the impact of processing steps on Campylobacter concentrations. Primary processing reduced Campylobacter concentrations on carcasses by almost 6-log; the biggest reduction was achieved by the spinchill, followed by the scald step. Significant plant differences in the degree of Campylobacter reduction were also observed at these steps. The spinchill and final acidified sodium chlorite wash resulted in carcasses with low-to-no levels of Campylobacter regardless of concentrations at prior steps. A similar study was conducted at primary processing for one plant in 2013; significant improvements in Campylobacter mitigation since 2013 were noted. Campylobacter concentrations from final product from secondary processing were higher than concentrations at the end of primary processing. Drumsticks had lower Campylobacter concentrations than other portion types. Skin removal from product did not consistently result in product with lower Campylobacter concentrations. Results identify key areas to target for further reduction of Campylobacter on poultry meat, and provide a benchmark to compare the efficacy of future interventions. Highlights: Primary processing reduced Campylobacter concentrations on carcasses by ∼6-log. Campylobacter was not recovered from 76% of samples at the end of primary processing. Campylobacter concentrations were higher on product at secondary processing. Drumsticks had lower Campylobacter concentrations than all other portion types. Skin removal did not result in lower Campylobacter concentrations on portions.